2019
DOI: 10.1088/1361-6528/ab176f
|View full text |Cite
|
Sign up to set email alerts
|

Anisotropic deformation of NiO nanoparticles embedded in silica under swift heavy ion irradiation

Abstract: We report on the ion-induced anisotropic deformation in nickel oxide nanoparticles prepared by conventional sol-gel technique. Colloidal-like NiO nanoparticles with an average diameter of about 40–50 nm embedded in a SiO2 layer change their shape dramatically under swift heavy ion irradiation with 32 MeV Cu+5 ions at room temperature and normal incidence. Transmission electron microscopy analysis show irradiation induced shape transformation from nearly spherical nanoparticles into oblate nanorods at a rate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 48 publications
0
5
0
Order By: Relevance
“…It is believed that the realization of elongation requires several basic conditions as follows: the high enough energy (hundreds of MeV) and proper fluence (≈10 13 ions cm −2 ) of implanted ions to form the ion tracks in the dielectrics; the larger diameter of NPs than the width of tracks (usually larger than 10 nm); and the suitable dielectrics. [ 90–102 ] It should be noted that the size condition of NPs for elongation is still under debate; and some experimental and theoretical studies on smaller NPs for effective elongation have been reported. [ 81 ] In this way, the NP–dielectrics systems can be well designed with tunable physical properties by optimizing the parameters during ion beam processing.…”
Section: Ion Beam Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…It is believed that the realization of elongation requires several basic conditions as follows: the high enough energy (hundreds of MeV) and proper fluence (≈10 13 ions cm −2 ) of implanted ions to form the ion tracks in the dielectrics; the larger diameter of NPs than the width of tracks (usually larger than 10 nm); and the suitable dielectrics. [ 90–102 ] It should be noted that the size condition of NPs for elongation is still under debate; and some experimental and theoretical studies on smaller NPs for effective elongation have been reported. [ 81 ] In this way, the NP–dielectrics systems can be well designed with tunable physical properties by optimizing the parameters during ion beam processing.…”
Section: Ion Beam Synthesis Of Nanoparticlesmentioning
confidence: 99%
“…20 Moreover, an anisotropic deformation observed by Dawi and his co-workers in NiO nanoparticles within silica when subjected to 32 MeV Cu ion irradiation. 21 The collective findings from these investigations highlight the diverse effects of Ag ion irradiation over other ions (such as Au and Cu) on NiO thin films, laying the z E-mail: vsharma.ph@doonuniversity.ac.in ECS Journal of Solid State Science and Technology, 2024 13 013009 groundwork for continued exploration and applications in the realms of material science and engineering.…”
mentioning
confidence: 92%
“…A number of theoretical models, and experimental investigation have been reported based on the ion-beam-induced NP reshaping [16][17][18][19][20][21][22][23]. So far, most of the published research only concerns amorphous silica as a matrix, and it is believed that the elongation of embedded NPs could be induced in amorphous materials only [24][25][26][27][28][29]. However, a much debated question still exists as to whether NPs can be elongated in the crystalline matrix.…”
Section: Introductionmentioning
confidence: 99%